Étude sur la phénoménologie de la réalité et de sa représentation idéelle dans la société civile - Marcienne Martin (Communication)
Evoking reality as a concept means looking at individuals’ perceptions of it through a given object in the world considered in a given context. The way reality and its correlates are decoded also differs from one sociocultural system to the next. Through denial, factual revisionism, and the use of lexical semantic procedures like metonymy, powers of various kinds can establish new social values in a given society. The phenomenon is illustrated in George Orwell’s 1984.